2021
DOI: 10.1029/2020ef001930
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective and Prospective Examination of the 1960s U.S. Northeast Drought

Abstract: As the most severe drought over the Northeastern United States (NEUS) in the past century, the 1960s drought had pronounced socioeconomic impacts. Although it was followed by a persisting wet period, the conditions leading to the 1960s extreme drought could return in the future, along with its challenges to water management. To project the potential consequences of such a future drought, pseudo-global warming simulations using the Weather Research and Forecasting Model are performed to simulate the dynamical c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Our drought trend results for 1921-2020 are generally consistent with McCabe et al (2017), who found that drought frequency has mostly declined across CONUS from 1901 to 2014. Decreases in drought duration and deficit in the northeastern CONUS during the 1951-2020 period overlap with the hydrologic step change observed around 1970 (McCabe & Wolock, 2002) and are likely due to dry conditions during the early parts of this period, such as the 1960s drought (Xue & Ullrich, 2021).…”
Section: Changes In Drought Through Timementioning
confidence: 76%
“…Our drought trend results for 1921-2020 are generally consistent with McCabe et al (2017), who found that drought frequency has mostly declined across CONUS from 1901 to 2014. Decreases in drought duration and deficit in the northeastern CONUS during the 1951-2020 period overlap with the hydrologic step change observed around 1970 (McCabe & Wolock, 2002) and are likely due to dry conditions during the early parts of this period, such as the 1960s drought (Xue & Ullrich, 2021).…”
Section: Changes In Drought Through Timementioning
confidence: 76%
“…For example, the 1930s “dust bowl” drought (drought 1) and the 1950s drought (drought 2) are two of the most well‐known and impactful droughts in the CONUS during the 20th century (Heim, 2017). The December 1962 through October 1968 drought (drought 3) was the most severe drought in the northeastern CONUS in the past century (Xue and Ullrich, 2021). The 1960s drought was associated with low streamflow across much of the northeastern CONUS and includes the drought of record in the Delaware River basin which supplies New York City and Philadelphia with drinking water (Kauffman and Vonck, 2011; Delaware River Basin Commission, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the Northeast US and elsewhere, climate change is leading to an increase in the frequency of extreme precipitation events in the form of flood and waterlogging events and intense short-and mediumduration droughts. 16,17 Therefore, understanding how environmental stressors associated with climate change may affect the range of variation in phytoestrogen concentrations in red clover has important implications for animal agriculture and human health.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phytoestrogens are thought to play a role in plant defense, serving to protect plants from environmental stress as well as perform roles in plant–microbe signaling and a range of other physiological functions. , Given their potential responsiveness to environmental variation, it is conceivable that the phytoestrogen concentrations in forage legumes such as red clover may be mediated by changes in environmental conditions associated with climate change. In the Northeast US and elsewhere, climate change is leading to an increase in the frequency of extreme precipitation events in the form of flood and waterlogging events and intense short- and medium-duration droughts. , Therefore, understanding how environmental stressors associated with climate change may affect the range of variation in phytoestrogen concentrations in red clover has important implications for animal agriculture and human health.…”
Section: Introductionmentioning
confidence: 99%